Ethnobotanical Study of Some Medicinal Species Used in Kimvula City (Kongo Central/ RDC) - Lassa, L. K.; Ilumbe, G. B.; Biloso, A. M.; Masens, D. M. Y.; Habari, JP. M.; Lukoki, F. L. (European Scientific Journal, ESJ, 2021)
This study has been conducted at Kimvula city. The goal was to investigate the medicinal plants used in that city. Thus, any ethnobotanical survey has been realized on the use of the plants in six towns by direct interviews among 180 peoples with an average of age comprise between 17- 70 years old with high representatives of women. This study has allowed us to establish a floristic list of 188 medicinal species belonging in 158 genera and 69 families where Fabaceae dominant group. Anemia was indications mostly cited as a sickness threated by using plants. Concerning the characteristics of the treatment preparation, leaves are the plant’s organs mostly used; decoction is the preparation way cited and the oral admistration is the administration way for those medicinal drugs. Morinda morindoides, Ocimum gratissimum, Disphania ambrosioïdes and Moringa oleifera have the VAUs superior or eaual to 1.10. There is not a link concerning the use of plants between the inhabitant of group 1 and the inhabitant of group 2. By the wah, that there is a link concerning the use of plants between the Lona, Winda, Pado, Revolution and Kinata neighborhoods (Group 2). Three sspcies characterized the group 1 like: Clematis hirsuta, Saccharum officinarum and Voacanga africana, and four especies Ceiba pentandra, Indigofera paracapitata, Maprounea africana and Ochna afzelii characterized the group 2.